A photo-inducible protein–inorganic nanoparticle assembly for active targeted tumour theranostics. Issue 13 (14th March 2019) - Xie, Jinbing; Mei, Ling; Huang, Kai; Sun, Yuxiang; Iris, Aarushi; Ma, Baoliang; Qiu, Yining; Li, Junjie; Han, Gang
Abstract : Protein–inorganic nanoparticles were formed under photo-illumination for tumor theranostics. Abstract : The assembly of protein–inorganic nanoparticles is an important yet challenging approach that is utilized to develop functional materials in numerous areas, such as bio-catalysis, drug delivery, and biosensing. In this study, we report on a facile, photo-inducible self-assembly method to generate protein–inorganic hybrid nanoplatforms. More specifically, photo-treated disulfide bond rich proteins of lysozyme (LYS) were able to be used as host materials in order to encapsulate nanoparticles ( i.e., as-synthesized hydrophobic NIR quantum dots (QDs)) and anti-cancer small molecule drugs ( i.e., paclitaxel (PTX)), constructing functional theranostic protein–inorganic hybrid nanoparticles. The modification of the functional polymer of cRGD–PEG contributes to the active tumour targeting characteristic of this protein–inorganic nanocarrier. This novel PTX loaded protein–inorganic hybrid nanoplatform showed high tumour homing accumulation as well as effective tumour inhibition. We believe that this general approach represents a new direction for the development of a photo-induced assembly of protein–inorganic nanoparticles towards versatile applications in both materials science and biomedical fields.